Engagement of CD147 molecule-induced cell aggregation through the activation of protein kinases and reorganization of the cytoskeleton - Khunkeawla P. (2014)
CD147 is a broadly expressed cell surface molecule of the immunoglobulin superfamily whose expression is up-regulated upon T cell activation. Engagement of CD147 by CD147 monoclonal antibodies (mAbs) has been shown to induce homotypic aggregation of U937 cells. To study intracellular signal transduction induced by the engagement of CD147 molecules, protein kinase C (PKC) and protein tyrosine kinase (PTK) inhibitors were used to inhibit cell aggregation. The results indicated that a PKC inhibitor, sphingosine, and a PTK inhibitor, herbimycin A, inhibited CD147 mAb-induced cell aggregation in a dose-dependent manner. In contrast to herbimycin A, a PTK inhibitor, genistein, enhanced cell aggregation. This discrepancy may be due to the differential effect of herbimycin A and genistein on the target cells. Effect of actin filament polymerization blocking agent, cytochalasin B, was also studied and it was found that cytochalasin B completely inhibited CD147 mAb-induced cell aggregation. This result implied that U937 cell aggregation induced by CD147 mAbs is associated with cytoskeleton reorganization. Thus, our observations suggest that cell aggregation induced by the engagement of CD147 with specific mAbs depend upon the activation of protein kinases and a functional cytoskeleton.